(untitled) (Research, Society and Development, 2018)
This text brings reflections on aspects involved in the development of policies of the Union, in collaboration, for the elaboration of the National Education Plan and evaluation of school performance, focusing on the municipal education systems of Duque de Caxias / RJ, Niterói / RJ and Queimados / RJ. Only the competencies included in items I and VI of article 9 of LDBEN 9394/96 (BRASIL, 1996) were considered.. The theoretical-methodological course of the research was based on the analysis of the policy cycle of S. Ball (1992, 2009) and their considerations on the active interpretation, in the local context, of the discourse of national educational policies. In the contexts investigated, it is possible to say that actions responsive to federal policies, even resulting from the process of intensifying the impact of national policies and programs in the local context, are also due to municipal political and administrative autonomy.